A revision of the genus Baeocera in Japan, with a new genus of the tribe Scaphisomatini (Coleoptera, Staphylinidae, Scaphidiinae) - Ogawa, Ryo; Löbl, Ivan (Zootaxa, 2013)
The Japanese species of the genus Baeocera Erichson, 1845 are reviewed and a new genus Baeoceroxidium is established for Baeocera micros (Achard, 1923) and members of the Baeocera pilifera species group. The female genitalia are used for the first time in Baeocera for both, as species specific characteristics and to indicate relationships. Amaloceroschema Löbl, 1967 is placed in synonymy with Baeocera.